THE IMPLEMENTATION OF PBL AND IBL COLLABORATION MODELS USING VIDEO TO IMPROVE STUDENTS’ CRITICAL THINKING - Yunitasari, Yessyca (EDUTECH, 2020)
Teaching history not only conveys historical facts but develops students' critical thinking in reconstructing historical events and the values contained therein. But the media and methods used today have not been able to improve students' critical thinking skills. This study aims to improve students' critical thinking skills through the application of PBL and IBL collaboration models using video. Research subjects are 10th grade students in one of the high school in Jember. The design of this study uses classroom action research consisting of three cycles. The results showed that the ability to think critically increased in each cycle. In cycle 1, the ability to think critically 50,33% in cycle 2 increased to 69,83% in cycle 3 increased to 78,38%. So it can be concluded that the application of the PBL and IBL collaboration models using video media can improve students' critical thinking skills.Pengajaran sejarah bukan hanya menyampaikan fakta-fakta sejarah tetapi mengembangkan pemikiran kritis siswa dalam merekonstruksi peristiwa sejarah dan nilai yang terkandung didalamnya. Namun media dan metode yang digunakan saat ini belum mampu meningkatkan kemampuan berpikir kritis siswa. Penelitian ini bertujuan untuk meningkatkan kemampuan berpikir kritis siswa melalui penerapan model kolaborasi PBL dan IBL menggunakan video. Subjek penelitian adalah siswa kelas X salah satu SMA di Jember. Desain penelitian ini menggunakan penelitian tindakan kelas yang terdiri dari tiga siklus. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis mengalami peningkatan di tiap siklusnya. Pada siklus 1 kemampuan berpikir kritis 50,33% pada siklus 2 meningkat menjadi 69,83% pada siklus 3 meningkat menjadi 78,38%. Jadi dapat disimpulkan bahwa penerapan model kolaborasi PBL dan IBL menggunakan media video mampu meningkatkan kemampuan berpikir kritis siswa.